Fathers and sons in Shakespeare : the debt never promised - Tromly, Fred B., 1943- (Book collections on Project MUSE., 2010)
Through careful scrutiny of word and deed, the scholarship in Fathers and Sons in Shakespeare reveals the complex attitude Shakespeare's sons harbour towards their fathers.